2015
DOI: 10.1186/s13075-015-0747-6
|View full text |Cite
|
Sign up to set email alerts
|

On the predictive utility of animal models of osteoarthritis

Abstract: Animal models of osteoarthritis are extensively used for investigating disease pathways and for preclinical testing of novel therapies. Their predictive utility, however, has often been questioned, mainly because preclinical efficacy of novel therapeutics is poorly translated in clinical trials. In the current narrative review, we consider the preclinical models that were used to support undertaking clinical trials for disease-modifying osteoarthritis drugs, and compare outcomes between clinical and preclinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
117
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(120 citation statements)
references
References 168 publications
2
117
0
1
Order By: Relevance
“…Thus drug development programs fail predominantly because their biological rationale, which is largely defined by preclinical research, was insufficient. The reasons underlying the inadequacy of this "starting evidence" are manifold and include issues with the conduct and reporting of pre-clinical research 9 . However rather than arguing for less pre-clinical research, the data on the reasons for drug development failures suggest greater emphasis on basic research to better understand disease pathophysiology and therapeutic target biology will improve subsequent clinical success.…”
Section: The Argument For "Mice"mentioning
confidence: 99%
“…Thus drug development programs fail predominantly because their biological rationale, which is largely defined by preclinical research, was insufficient. The reasons underlying the inadequacy of this "starting evidence" are manifold and include issues with the conduct and reporting of pre-clinical research 9 . However rather than arguing for less pre-clinical research, the data on the reasons for drug development failures suggest greater emphasis on basic research to better understand disease pathophysiology and therapeutic target biology will improve subsequent clinical success.…”
Section: The Argument For "Mice"mentioning
confidence: 99%
“…However, few, if any, therapeutics developed in this manner have successfully completed double-blinded, placebo-controlled clinical trials (Huggins et al, 2012;Malfait and Little, 2015;Miller et al, 2014). While a number of issues have been identified that could underlie the limited translation of preclinical findings to a clinical treatment, one issue could be the use of rodents, which are phylogenetically distant to humans.…”
Section: Introductionmentioning
confidence: 97%
“…В результате, активируются NF-kB рецепторы синовиальных фибробластов, что определя-ет высвобождение многих цитокинов, таких как ИЛ-6, ИЛ-10, GM-CSF, IL-8 и хемоаттрактант моноцитов, кото-рый, в свою очередь, играет значимую роль в актива-ции металлопротеиназ и обуславливает их высокую активность при остеоартрозе [6][7][8][9].…”
unclassified